2018
DOI: 10.7717/peerj.4703
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of soil salinity by means of different modeling methods and visible-near infrared (VIS–NIR) spectroscopy, Ebinur Lake Wetland, Northwest China

Abstract: Soil salinization is one of the most common forms of land degradation. The detection and assessment of soil salinity is critical for the prevention of environmental deterioration especially in arid and semi-arid areas. This study introduced the fractional derivative in the pretreatment of visible and near infrared (VIS–NIR) spectroscopy. The soil samples (n = 400) collected from the Ebinur Lake Wetland, Xinjiang Uyghur Autonomous Region (XUAR), China, were used as the dataset. After measuring the spectral refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 63 publications
2
72
0
1
Order By: Relevance
“…Random forest (RF) is a machine learning method widely used in the field of classification and regression in recent years [25]. Multiple soil properties have been linked to the Vis-NIR spectrum through this algorithm, such as soil organic carbon (SOC) [26], soil cadmium (Cd) [27], forage phosphorus (P) [28] and soil pH [29]. Numerous research results indicate that RF provides better prediction results than the classical partial least-squares regression (PLSR) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Random forest (RF) is a machine learning method widely used in the field of classification and regression in recent years [25]. Multiple soil properties have been linked to the Vis-NIR spectrum through this algorithm, such as soil organic carbon (SOC) [26], soil cadmium (Cd) [27], forage phosphorus (P) [28] and soil pH [29]. Numerous research results indicate that RF provides better prediction results than the classical partial least-squares regression (PLSR) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple soil properties have been linked to the Vis-NIR spectrum through this algorithm, such as soil organic carbon (SOC) [26], soil cadmium (Cd) [27], forage phosphorus (P) [28] and soil pH [29]. Numerous research results indicate that RF provides better prediction results than the classical partial least-squares regression (PLSR) [29][30][31]. Furthermore, compared to other machine learning technologies such as artificial neural networks (ANN) and support vector machine (SVM), the RF model can provide the relative importance of each predictor, which makes the results of the model highly interpretable [27,32].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al used the PLSR algorithm and the random forest (RF) algorithm to measure soil salinity. According to the validation accuracies, the RF models outperformed the PLSR models [34]. These studies were conducted in different data and different environments, and the results obtained cannot be put together for comprehensive evaluation of these models.…”
Section: Introductionmentioning
confidence: 99%
“…The regularization can reduce the influence of collinearity by adding offset to the optimization function [30]. With the deep research of machine learning methods, the results are uneven and many studies in which machine learning methods are used to estimate soil salinity have been reported [4,21,24,[32][33][34]. Jiang et al monitored soil salinity by integrating multiple biophysical indicators with support vector machine (SVM) and artificial neural network (ANN) regression algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hyperspectral inversion models established for available potassium are mainly constructed based on 1-order or 2-order derivative for spectral reflectance, reciprocal, and logarithm. However, related research points out that traditional integer-order differential transformation ignores the gradual fractional differential information [18,19], especially for high-dimensional data sources such as hyperspectral images with massive information, which may cause some information to be lost or be difficult to extract, and restrict the modeling accuracy.Fractional calculus theory is a mathematical problem for studying the properties of differential and integral operators of any order and its application. First proposed in 1695, its development is almost in synchronization with the theory of integer-order calculus.…”
mentioning
confidence: 99%